Analysis of Rubberized Concrete Deck Slab for Different Bridge Structures as Per IRC Loadings A Review - Ankit Patel; Murlidhar Chourasiya (International Journal of Scientific Research in Civil Engineering, 2022)
In this research work the finite element method is used for the analysis of three different type of bridges i.e. cable stayed, cable suspension and deck bridge with rubberized and NaOH treated rubberized concrete of constant width and length is considered.In this paper we are presenting review of literatures related to analysis of bridge tructure with material variations.
Keywords: F.E.M; Structural Analysis; Bridge; Deck Slab; Hydraulic Design; Vehicular Loading; I.R.C.; Staad Beava; Forces; Rubberized Concrete